A case study on the community acceptance and satisfaction of electronic services (E-Service) / Noradilah Zakariah - Zakariah, Noradilah (2005)
Government increasingly turn to the hitemet's as a medium for communication and publishing information related to the delivery of the public service. As the technologies continue to evolve, the government is expanding their use of this technology by providing services on the web with which the public can interact and conduct business. Rather than relying on employees to respond to inquiries or process requests for information, through the use of electronic government, the public can "serve themselves" to a wide variety of the information and services. For a research on a Case Study On The Community Acceptance And Satisfaction Of Electronic Services (EService), a set of questionnaires was distributed throughout the peninsular Malaysia especially in Pahang and Selangor. The purpose of the questionnaires (completed by 100 people) was to obtain the views of citizen's acceptance and their level of satisfaction of using electronic services, to make a comparison between traditional channel (counter) and online in the way people used and locate the government services and information and to analyze the requirement for the establishment of electronic services that will allow the government to improve services to the people through the use of the current technology. The result indicates that government has lots more to improved through their services and that people are willing to use government electronic services if the services provided is reliable and secured in terms of the transaction and the information.